(untitled) (Research, Society and Development, 2020)
The epidermoid cyst is a relatively common non-odontogenic cyst that has its origin related to the implantation of epithelial remains during the fusion of embryonic processes. This article aims to report a case of epidermoid cyst in the mandibular region, with emphasis on its diagnosis and clinical conduct. The young adult patient presented an increase in volume in the region of the right mandibular body. The lesion was removed by means of simple surgical excision, under local anesthesia, and the piece sent for histopathological analysis, in order to confirm the clinical hypothesis of an epidermoid cyst. During follow-up, reinterventions were not necessary, demonstrating that it is an easily resolved lesion, through a simple surgical procedure.